Laminated film and method for manufacturing semiconductor device
By using a specific melting agent compound in the adhesive layer of the layer -layer membrane, the problem of reduced welds after the welded metal wettability is reduced for a long time under the room temperature environment, and the stability and reliability of the connection part are realized.
Patent Information
- Application Number
- CN202380045368.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-05
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-21
AI Technical Summary
The laminated film used after being placed for a long time under a room temperature environment leads to a problem of degradation of the wettability of the solder to the metal to the connecting portion.
The melting agent compounds with 2 carboxyl groups, such as a compound with an atomic number of 4, 6 or 8 or above with the aromatic ring, the adulh ring or the main chain. The pressure -sensitive adhesion layer.
Even after a long time in room temperature, it can still effectively suppress the reduction of welds on the metal wetting of the connection to ensure the reliability of the connection.
Smart Images

Figure CN119343420A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a stacked film and a semiconductor device. Background Art
[0002] Conventionally, when a semiconductor chip and a substrate are connected, a wire bonding method using a thin metal wire such as a gold wire is widely used.
[0003] In recent years, in order to meet the requirements for higher functionality, higher integration, and higher speed of semiconductor devices, a flip chip connection method (FC connection method) has been spreading, in which conductive protrusions called bumps are formed on a semiconductor chip or a substrate to directly connect the semiconductor chip to the substrate.
[0004] For example, regarding the connection between a semiconductor chip and a substrate, the COB (Chip On Board) type connection method widely used in BGA (Ball Grid Array) and CSP (Chip Size Package) also belongs to the FC connection method. In addition, the FC connection method is also widely used in the COC (Chip On Chip) type connection method in which a connection portion (bump or wiring) is formed on a semiconductor chip to connect between semiconductor chips, and the COW (Chip On Wafer) type connection method in which a connection portion (bump or wiring) is formed on a semiconductor wafer to connect between a semiconductor chip and a semiconductor wafer (for example, refer to Patent Document 1).
[0005] In addition, in the packaging that has a strong demand for further miniaturization, thinning and high functionality, chip stacking packages, POP (Package On Package), TSV (Through-Silicon Via), etc., which stack / multi-level the above-mentioned connection methods, have also begun to become widely popular. In this stacking / multi-level technology, semiconductor chips and the like are arranged three-dimensionally, so the package can be reduced compared to the two-dimensional arrangement method. In addition, since it is also effective in improving semiconductor performance, reducing noise, reducing mounting area, and saving power, it has attracted attention as the next generation of semiconductor wiring technology.
[0006] Previous technical literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2012-222038 Summary of the invention
[0009] Technical issues to be solved by the invention
[0010] In recent years, there has been a demand for higher density and higher speed packaging for high-performance mobile devices and the like, and three-dimensional packaging using through silicon vias (TSVs) that achieve high-speed communication by shortening wires has attracted attention.
[0011] In the above-mentioned package, the number of stacked semiconductor devices tends to increase with the trend of high integration and miniaturization. As a method for manufacturing such a semiconductor device, a stacked film stacked with a film adhesive and a backgrind tape is attached to a semiconductor wafer with bumps in advance, and the semiconductor wafer is thinned and then singulated into individual semiconductor chips.
[0012] Furthermore, in the above-mentioned package, in order to achieve large capacity and high-speed communication, the space between the bumps is narrowed, so there is a tendency to easily produce reduced embedding and deteriorated wettability. In order to solve this problem, the film adhesive (adhesive layer) in the above-mentioned laminated film is required to have high fluidity. In order to be applied to such narrow gap and narrow pitch packages, a laminated film having an adhesive layer that achieves slow curing and high fluidity has been developed. However, if this laminated film is used after being left for a long time at room temperature, when the connecting part of the semiconductor chip is connected to the connecting part of the wiring circuit substrate, the semiconductor wafer or the connecting part of another semiconductor chip, there is a problem that the wettability of the metal of the connecting part by the solder is easily deteriorated.
[0013] Therefore, an object of the present invention is to provide a laminated film and a method for manufacturing a semiconductor device that can suppress a decrease in wettability of solder to metal at a connection portion even when the laminated film and the semiconductor device are used after being left for a long period of time in a room temperature environment.
[0014] Means for solving technical problems
[0015] The present inventors have repeatedly conducted in-depth research to solve the above-mentioned problems, and as a result, found that when a laminated film having an adhesive layer that achieves slow curing and high fluidity is used after being left for a long time in a room temperature environment, the reason why the wettability of the metal of the connection portion by the solder decreases is because the flux compound in the adhesive layer is transferred to the pressure-sensitive adhesive layer of the back grinding tape over time. In addition, the present inventors have studied the types of flux compounds that can suppress the transfer of the flux compound to the pressure-sensitive adhesive layer of the back grinding tape over time, and found that by using a specific flux compound, the wettability of the metal of the connection portion by the solder can be suppressed even when the laminated film is used after being left for a long time in a room temperature environment, and thus completed the present invention.
[0016] That is, the present invention provides the following method for manufacturing a laminated film and a semiconductor device.
[0017] [1] A laminated film comprising an adhesive layer, a pressure-sensitive adhesive layer, and a substrate layer in this order, wherein the adhesive layer comprises a thermoplastic resin, a thermosetting resin, a curing agent, and a flux compound having two carboxyl groups, wherein:
[0018] The flux compound includes at least one selected from the group consisting of a compound having an aromatic ring, a compound having an aliphatic ring, and a compound having 4, 6, or 8 or more constituent atoms in a main chain.
[0019] [2] The laminated film according to [1] above, wherein
[0020] In the compound having 4, 6 or 8 or more constituent atoms in the main chain, the number of constituent atoms in the main chain is 4, 6 or 8.
[0021] [3] The laminated film according to [1] or [2] above, wherein
[0022] The compound having 4, 6 or 8 or more constituent atoms in the main chain includes a compound represented by the following general formula (1).
[0023]
[0024] [In formula (1), R 1 represents a hydrogen atom or a monovalent organic group, n represents an integer of 4, 6 or 8 to 14, and there are plural R 1 They may be the same or different from each other.]
[0025] [4] The laminated film according to any one of [1] to [3] above, wherein
[0026] The compound having 4, 6 or 8 or more constituent atoms in the main chain includes a compound represented by the following general formula (2).
[0027]
[0028] [In formula (2), n represents an integer of 4, 6 or 8 to 14.]
[0029] [5] The laminated film according to any one of [1] to [4] above, wherein
[0030] The melting point of the above flux compound is 100 to 160°C.
[0031] [6] The laminated film according to any one of [1] to [5] above, wherein
[0032] The above-mentioned thermosetting resin includes epoxy resin.
[0033] [7] The laminated film according to any one of [1] to [6] above, wherein
[0034] The curing agent includes an amine curing agent.
[0035] [8] The laminated film according to any one of [1] to [7] above, wherein
[0036] The curing agent includes an imidazole-based curing agent.
[0037] [9] A method for manufacturing a semiconductor device, wherein the semiconductor device is a semiconductor device in which the connection portions of a semiconductor chip and a wiring circuit substrate are electrically connected to each other, or a semiconductor device in which the connection portions of a plurality of semiconductor chips are electrically connected to each other, the method for manufacturing a semiconductor device comprising: a step of bonding the surface of the adhesive layer side of the laminate film described in any one of [1] to [8] to a semiconductor wafer; a step of back grinding the semiconductor wafer; and a step of singulating the semiconductor wafer to obtain a semiconductor chip with an adhesive layer; and a step of attaching the semiconductor chip to a wiring circuit substrate, a semiconductor wafer or another semiconductor chip via the adhesive layer.
[0038]
[10] The method for manufacturing a semiconductor device according to [9] above, wherein:
[0039] The process of attaching the above-mentioned semiconductor chip to a wiring circuit substrate, a semiconductor wafer or another semiconductor chip via the above-mentioned adhesive layer includes: a process of arranging a plurality of the above-mentioned other semiconductor chips on a workbench; and a temporary fixing process of heating the above-mentioned workbench to 60-155°C and arranging the above-mentioned semiconductor chip in sequence on each of the plurality of the above-mentioned other semiconductor chips arranged on the above-mentioned workbench via the above-mentioned adhesive layer to obtain a plurality of stacked bodies formed by sequentially stacking the above-mentioned other semiconductor chips, the above-mentioned adhesive layer and the above-mentioned semiconductor chips.
[0040]
[11] The method for manufacturing a semiconductor device according to [9] above, wherein:
[0041] The process of attaching the above-mentioned semiconductor chip to a wiring circuit substrate, a semiconductor wafer or another semiconductor chip via the above-mentioned adhesive layer includes: a process of configuring the above-mentioned wiring circuit substrate or the above-mentioned semiconductor wafer on a workbench; and a temporary fixing process of heating the above-mentioned workbench to 60-155°C and sequentially configuring a plurality of the above-mentioned semiconductor chips on the above-mentioned wiring circuit substrate or semiconductor wafer configured on the above-mentioned workbench via the above-mentioned adhesive layer to obtain a stacked body formed by sequentially stacking the above-mentioned wiring circuit substrate, the above-mentioned adhesive layer and the plurality of the above-mentioned semiconductor chips, or a stacked body formed by sequentially stacking the above-mentioned semiconductor wafer, the above-mentioned adhesive layer and the plurality of the above-mentioned semiconductor chips.
[0042] Effects of the Invention
[0043] According to the present invention, it is possible to provide a laminated film and a method for manufacturing a semiconductor device that can suppress a decrease in wettability of solder to metal at a connection portion even when the laminated film and the semiconductor device are used after being left for a long period of time in a room temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a schematic cross-sectional view showing one embodiment of a laminated film.
[0045] Figure 2 is the FT-IR spectrum of glutaric acid.
[0046] Figure 3 is the FT-IR spectrum of adipic acid.
[0047] Figure 4 It is a schematic cross-sectional view showing one embodiment of a semiconductor device according to the present invention.
[0048] Figure 5 It is a schematic cross-sectional view showing another embodiment of the semiconductor device according to the present invention.
[0049] Figure 6 It is a schematic cross-sectional view showing another embodiment of the semiconductor device according to the present invention.
[0050] Figure 7 This is a circuit diagram of a semiconductor chip used in connectivity evaluation.
[0051] Figure 8 The BGT extract obtained from the initial laminated film of Comparative Example 1, the BGT extract obtained from the laminated film of Comparative Example 1 after being left for 4 weeks, and the glutaric acid 1 H-NMR spectrum.
[0052] Fig. 9 The BGT extract obtained from the initial laminated film of Example 1, the BGT extract obtained from the laminated film of Example 1 after being left for 4 weeks, and the adipic acid 1 H-NMR spectrum. DETAILED DESCRIPTION
[0053] Hereinafter, an embodiment of the present invention will be described in detail with reference to the accompanying drawings as appropriate. In addition, in the accompanying drawings, the same or equivalent parts are marked with the same symbols, and repeated descriptions are omitted. Furthermore, regarding the positional relationship such as up, down, left, and right, unless otherwise specified, it is based on the positional relationship shown in the accompanying drawings. In addition, the dimensional ratios of the accompanying drawings are not limited to the ratios shown in the drawings.
[0054] The upper limit and lower limit of the numerical range described in this specification can be arbitrarily combined. The numerical values described in the examples can also be used as the upper limit or lower limit of the numerical range. In this specification, "(meth)acrylic acid" means acrylic acid or its corresponding methacrylic acid.
[0055] <Laminated film>
[0056] Figure 1 Schematic cross-sectional view showing one embodiment of the laminated film according to the present invention. Figure 1 As shown, the laminated film 10 according to this embodiment includes an adhesive layer (film adhesive) 1 and a back grinding tape 4 composed of a substrate layer 2 and a pressure-sensitive adhesive layer 3. The laminated film may include a substrate film on the surface of the adhesive layer 1 opposite to the pressure-sensitive adhesive layer 3.
[0057] (Adhesive layer 1)
[0058] The adhesive layer includes (a) a thermoplastic resin (hereinafter, sometimes referred to as "component (a)"), (b) a thermosetting resin (hereinafter, sometimes referred to as "component (b)"), (c) a curing agent (hereinafter, sometimes referred to as "component (c)"), and (d) a flux compound having two carboxyl groups (hereinafter, sometimes referred to as "component (d)"). The adhesive layer may further include (e) a filler (hereinafter, sometimes referred to as "component (e)").
[0059] Hereinafter, each component constituting the adhesive layer will be described.
[0060] (a) Thermoplastic resin
[0061] As (a) component, it is not particularly limited, for example, phenoxy resin, polyimide resin, polyamide resin, polycarbodiimide resin, cyanate resin, acrylic resin, polyester resin, polyethylene resin, polyethersulfone resin, polyetherimide resin, polyvinyl acetal (polyvinyl acetal) resin, carbamate resin and acrylic rubber can be mentioned. Among them, from the viewpoint of excellent heat resistance and film formation, preferably phenoxy resin, polyimide resin, acrylic resin, acrylic rubber, cyanate resin and polycarbodiimide resin, more preferably phenoxy resin, polyimide resin and acrylic resin. These (a) components can be used alone, and can also be used in the form of a mixture or copolymer of two or more.
[0062] The weight average molecular weight (Mw) of component (a) is preferably 10,000 or more, more preferably 20,000 or more, and further preferably 25,000 or more. By means of this component (a), the film forming property and the heat resistance of the adhesive can be further improved. Moreover, when the weight average molecular weight is 10,000 or more, it is easy to impart flexibility to the film-like adhesive layer, so it is easy to obtain better processability. Moreover, the weight average molecular weight of component (a) is preferably 1,000,000 or less, more preferably 500,000 or less, and further preferably 100,000 or less. By means of this component (a), the viscosity of the film is reduced, so the embedding property of the bump becomes good, and it can be further installed without gaps. From these viewpoints, the weight average molecular weight of component (a) is preferably 10,000 to 1,000,000, more preferably 20,000 to 500,000, and further preferably 25,000 to 100,000.
[0063] In addition, in this specification, the weight average molecular weight means the weight average molecular weight in terms of polystyrene measured by using GPC (Gel Permeation Chromatography). An example of the measurement conditions of the GPC method is shown below.
[0064] Apparatus: HCL-8320GPC, UV-8320 (product name, manufactured by TOSOH CORPORATION) or HPLC-8020 (product name, manufactured by TOSOH CORPORATION)
[0065] Chromatographic column: TSKgel superMultiporeHZ-M×2, or 2 GMHXL + 1 G-2000XL
[0066] Detector: RI or UV detector
[0067] Column temperature: 25~40℃
[0068] Eluent: Select a solvent that dissolves the polymer component. Examples of the solvent include THF (tetrahydrofuran), DMF (N,N-dimethylformamide), DMA (N,N-dimethylacetamide), NMP (N-methylpyrrolidone), and toluene. In addition, when a polar solvent is selected, the concentration of phosphoric acid can be adjusted to 0.05 to 0.1 mol / L (usually 0.06 mol / L), and the concentration of LiBr can be adjusted to 0.5 to 1.0 mol / L (usually 0.63 mol / L).
[0069] Flow rate: 0.30~1.5mL / min
[0070] Standard material: polystyrene
[0071] (b) Content of ingredient C b The content of component (a) C a Ratio C b / C a (mass ratio) is preferably 0.01 or more, more preferably 0.1 or more, and further preferably 1 or more, and is preferably 5 or less, more preferably 4.5 or less, and further preferably 4 or less. b / C a When the ratio C is set to 0.01 or more, better curability and adhesion can be obtained. b / C a When the ratio is 5 or less, good film forming properties can be obtained. b / C a It is preferably 0.01 to 5, more preferably 0.1 to 4.5, and even more preferably 1 to 4.
[0072] From the viewpoint of improving connection reliability, the glass transition temperature of component (a) is preferably above -50°C, more preferably above -40°C, and further preferably above -30°C. From the viewpoint of lamination, it is preferably below 220°C, more preferably below 200°C, and further preferably below 180°C. The glass transition temperature of component (a) is preferably -50 to 220°C, more preferably -40 to 200°C, and further preferably -30 to 180°C. According to the adhesive layer containing such component (a), the amount of wafer warpage can be further reduced in the wafer-level mounting process, and the heat resistance and film forming properties of the adhesive layer can be further improved. The glass transition temperature of component (a) can be measured by differential scanning calorimetry (DSC).
[0073] The content of component (a) is preferably 30% by mass or less, more preferably 25% by mass or less, and further preferably 20% by mass or less, based on the total solid content of the adhesive layer. When the content of component (a) is 30% by mass or less, the adhesive layer can obtain good reliability during the temperature cycle test, and can obtain good adhesion at a reflow temperature of about 260°C even after moisture absorption. In addition, the content of component (a) is preferably 1% by mass or more, more preferably 3% by mass or more, and further preferably 5% by mass or more, based on the total solid content of the adhesive layer. When the content of component (a) is 1% by mass or more, the adhesive layer can further reduce the amount of wafer warpage in the wafer-level installation process, and can further improve the heat resistance and film formation of the adhesive layer. In addition, when the content of component (a) is 5% by mass or more, it is possible to suppress burrs and defects when the outer shape is processed into a wafer shape. From the above viewpoints and the viewpoint of easily imparting flexibility to the film-like adhesive layer and easily obtaining better processability, the content of component (a) is preferably 1 to 30% by mass, more preferably 3 to 30% by mass, and further preferably 5 to 30% by mass based on the total solid content of the adhesive layer. In addition, in this specification, the "total solid content of the adhesive layer" may be referred to as the "total amount of components (a) to (e)".
[0074] (b) Thermosetting resin
[0075] As component (b), any component having two or more reactive groups in the molecule can be used without particular limitation. Since the adhesive layer contains a thermosetting resin, the adhesive can be cured by heating, and the cured adhesive exhibits high heat resistance and adhesion to the chip, and excellent reflow resistance can be obtained.
[0076] As (b) component, for example, epoxy resin, phenolic resin, imide resin, urea resin, melamine resin, silicone resin, (meth) acrylic compound, vinyl compound can be cited. Among them, from the viewpoint of excellent heat resistance (reflow resistance) and storage stability, epoxy resin, phenolic resin and imide resin are preferred, epoxy resin and imide resin are more preferred, and epoxy resin is further preferred. These (b) components can be used alone, and can also be used in the form of a mixture or copolymer of two or more.
[0077] As epoxy resin and imide resin, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, naphthalene type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, phenol aralkyl type epoxy resin, biphenyl type epoxy resin, triphenylmethane type epoxy resin, dicyclopentadiene type epoxy resin and various multifunctional epoxy resins, nadimide resin, allyl nadimide resin, maleimide resin, amide imide resin, imide acrylate resin, various multifunctional imide resins and various polyimide resins can be used. These can be used alone or in the form of a mixture of two or more.
[0078] Regarding component (b), from the viewpoint of suppressing decomposition during connection at high temperature to generate volatile components, when the temperature during connection is 250°C, it is preferred to use a component with a thermal weight loss rate of 5% or less at 250°C, and when the temperature during connection is 300°C, it is preferred to use a component with a thermal weight loss rate of 5% or less at 300°C.
[0079] The content of component (b) is based on the total solid content of the adhesive layer, for example, 5% by mass or more, preferably 15% by mass or more, and more preferably 30% by mass or more. The content of component (b) is based on the total solid content of the adhesive layer, for example, 80% by mass or less, preferably 70% by mass or less, and more preferably 60% by mass or less. The content of component (b) is based on the total solid content of the adhesive layer, for example, 5 to 80% by mass, preferably 15 to 70% by mass, and more preferably 30 to 60% by mass.
[0080] (c) Curing agent
[0081] (c) component can be a curing agent that can form a salt with the flux compound described later. As (c) component, for example, amine curing agent (amines) and imidazole curing agent (imidazoles) can be cited. When (c) component contains amine curing agent or imidazole curing agent, it shows the activity of the flux that suppresses the generation of oxide film in the connection part, and can improve the connection reliability / insulation reliability. In addition, when (c) component contains amine curing agent or imidazole curing agent, the storage stability is further improved, and there is a tendency that decomposition or deterioration caused by moisture absorption is not easy to occur. In addition, when (c) component contains amine curing agent or imidazole curing agent, the adjustment of curing speed becomes easy, and it becomes easy to achieve a short-time connection for the purpose of improving productivity through rapid curing.
[0082] Hereinafter, each curing agent will be described.
[0083] (i) Amine curing agent
[0084] As the amine-based curing agent, for example, dicyandiamide can be used.
[0085] The content of the amine curing agent is preferably 0.1 parts by mass or more relative to 100 parts by mass of the above-mentioned component (b), and is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less. When the content of the amine curing agent is 0.1 parts by mass or more, there is a tendency for the curability to be improved. When it is 10 parts by mass or less, the adhesive layer will not cure before the metal joint is formed, and there is a tendency that poor connection is not likely to occur. From these viewpoints, the content of the amine curing agent is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the component (b), and more preferably 0.1 to 5 parts by mass.
[0086] (ii) Imidazole curing agent
[0087] Examples of the imidazole curing agent include 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyano-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6 -[2'-Undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole and adducts of epoxy resins and imidazoles. Among them, from the viewpoint of excellent curability, storage stability and connection reliability, 1-cyanoethyl-2-undecyl imidazole, 1-cyano-2-phenyl imidazole, 1-cyanoethyl-2-undecyl imidazole trimellitate, 1-cyanoethyl-2-phenyl imidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole and 2-phenyl-4-methyl-5-hydroxymethylimidazole are preferred. And, from the viewpoint of obtaining a more sufficient effect of the present invention, 2-phenyl-4,5-dihydroxymethylimidazole is preferred. These can be used alone or in combination of two or more. And, latent curing agents that microencapsulate these can also be used.
[0088] The content of the imidazole curing agent is preferably 0.1 parts by mass or more relative to 100 parts by mass of component (b), and preferably 10 parts by mass or less, more preferably 5 parts by mass or less. When the content of the imidazole curing agent is 0.1 parts by mass or more, there is a tendency for the curability to be improved. When the content of the imidazole curing agent is 10 parts by mass or less, the adhesive layer will not solidify before the metal joint is formed, so that poor connection is not likely to occur, and it is easy to suppress the generation of voids in the curing process under a pressurized atmosphere. From these viewpoints, the content of the imidazole curing agent is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of component (b), and more preferably 0.1 to 5 parts by mass.
[0089] The components (c) can be used alone or in the form of a mixture of two or more. For example, an imidazole curing agent can be used alone or in combination with an amine curing agent. As the component (c), a curing agent other than the above that functions as a curing agent for the component (b) can also be used.
[0090] The content of component (c) is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, relative to 100 parts by mass of component (b), and preferably 20 parts by mass or less, more preferably 6 parts by mass or less, and further preferably 5 parts by mass or less. When the content of component (c) is 0.2 parts by mass or more, there is a tendency to fully cure. When the content of component (c) is 20 parts by mass or less, the phenomenon of rapid curing and increased reaction points is suppressed, and there is a tendency to suppress the shortening of the molecular chain or the residual unreacted groups and the reduction of reliability. In addition, it becomes easy to suppress the phenomenon of residual voids during curing under a pressurized atmosphere. From these viewpoints, the content of component (c) is preferably 0.2 to 20 parts by mass, more preferably 0.5 to 6 parts by mass, and further preferably 0.5 to 5 parts by mass relative to 100 parts by mass of component (b).
[0091] The content of component (c) is preferably 0.5% by mass or more, based on the total solid content of the adhesive layer, and is preferably 2.3% by mass or less, and more preferably 2.0% by mass or less. When the content of component (c) is 0.5% by mass or more, there is a tendency to fully cure. When the content of component (c) is 2.3% by mass or less, the phenomenon of rapid curing and increased reaction points is suppressed, and there is a tendency to suppress the shortening of the molecular chain or the residual unreacted groups and the reduction of reliability. In addition, it becomes easy to suppress the phenomenon of residual voids during curing under a pressurized atmosphere. From these viewpoints, the content of component (c) is preferably 0.5 to 2.3% by mass, and more preferably 0.5 to 2.0% by mass, based on the total solid content of the adhesive layer.
[0092] (d) Flux compounds
[0093] The component (d) is a compound having flux activity (flux). When the adhesive layer contains the component (d), the metal oxide film and the coating based on the OSP treatment at the connection part can be removed, so that excellent connection reliability can be easily obtained.
[0094] (d) component includes at least one of the group consisting of compounds having an aromatic ring, a compound having an aliphatic ring, and a compound having a main chain (excluding the carboxyl group) with a constituent atom number of 4, 6 or 8 or more. By including the above-mentioned specific compound in the component (d), even if the laminated film is placed for a long time under room temperature and then used, the wettability of the metal of the connecting portion by the solder can be suppressed. This is because the movement of the above-mentioned specific compound in the adhesive layer is easily suppressed, and the movement from the adhesive layer to the pressure-sensitive adhesive layer is suppressed. By not transferring the component (d) from the adhesive layer to the pressure-sensitive adhesive layer but remaining in the adhesive layer, when the connecting portion of the semiconductor chip is connected to the connecting portion of the wiring circuit substrate, the semiconductor wafer or another semiconductor chip, the flux activity of the adhesive layer is fully manifested, and the wettability of the metal of the connecting portion by the solder can be suppressed.
[0095] It is considered that the pressure-sensitive adhesive layer in which compounds having aromatic rings, compounds having aliphatic rings, and compounds having 4, 6, or 8 or more constituent atoms in the main chain are difficult to transfer from the adhesive layer is due to their molecular structure. Since compounds having aromatic rings and compounds having aliphatic rings have ring structures, compounds with large volume and bulky structures become difficult to move in the adhesive layer, and as a result, they are difficult to transfer to the pressure-sensitive adhesive layer. In addition, compounds having 8 or more constituent atoms in the main chain also have long main chains, so they become difficult to move in the adhesive layer, and as a result, they are difficult to transfer to the pressure-sensitive adhesive layer. On the other hand, the reason why compounds having 4 or 6 constituent atoms in the main chain are difficult to transfer from the adhesive layer to the pressure-sensitive adhesive layer is as follows.
[0096] That is, the inventors found that the compound whose main chain has an even number of constituent atoms is suppressed in the movement within the adhesive layer compared with the compound whose main chain has an odd number of constituent atoms, and it is difficult to transfer to the pressure-sensitive adhesive layer. It is believed that this is because the compound whose main chain has an even number of constituent atoms is easy to form a cyclic dimer. In the case where the number of constituent atoms of the main chain is an even number, as shown in the following formula (I), in two compounds (in the following formula (I), the case of adipic acid with 4 constituent atoms of the main chain is shown), hydrogen bonds are formed between the carbonyl group of one compound and the hydroxyl group of another compound and between the hydroxyl group of one compound and the carbonyl group of another compound, respectively, and a cyclic dimer is easily formed. Since the cyclic dimer has a three-dimensional structure, it is difficult to pass through the polymer network of the (a) component in the adhesive layer compared with the monomer and chain dimer with a planar structure. In addition, the chain dimer is bonded at one end, and in contrast, the cyclic dimer is bonded at two ends, so the cyclic dimer is not easy to dissociate and is easy to stably exist in the state of a dimer. Therefore, it is believed that the movement of the compound with an even number of constituent atoms in the main chain is suppressed in the adhesive layer and is difficult to transfer to the pressure-sensitive adhesive layer. In addition, when the number of constituent atoms in the main chain is odd, as shown in the following formula (II), in two compounds (the following formula (II) shows the case of glutaric acid with a main chain of 3 constituent atoms), the carbonyl group of one compound is separated from the hydroxyl group of the other compound, so it is difficult to form a cyclic dimer. In the case of forming a dimer, as shown in the following formula (III), a chain dimer is easily formed. Therefore, it is believed that the compound with an odd number of constituent atoms in the main chain exists in the adhesive layer as a monomer or a chain dimer.
[0097]
[0098] FT-IR measurements of glutaric acid (number of atoms in the main chain: 3) and adipic acid (number of atoms in the main chain: 4) were performed to confirm the presence of these compounds. The measurement conditions were as follows, and the presence of the compounds was confirmed by comparing the measured and calculated FT-IR spectra.
[0099] (Measured)
[0100] The film-like adhesive layer was cut into a size of 1.0 cm × 1.0 cm as a sample, and the FT-IR spectrum of the sample surface was measured using an ALPHA compact infrared spectrometer (manufactured by Bruker Optics KK, ATR method). In the case of glutaric acid, the adhesive layer of Comparative Example 1 described below was used as the film-like adhesive layer, and the adhesive layer of Example 1 described below was used as the film-like adhesive layer.
[0101] (calculate)
[0102] The structure of the target flux compound was drawn using the molecular structure modeling software: "Chem3D", and the drawn structure was used to create an input file using the molecular structure modeling and calculation input file creation software: "Avogadro". The structure optimization and frequency calculation were performed using the quantum chemical calculation software (semi-empirical method, PM3): "Firefly". Based on the frequency calculation results, the IR spectrum was output using the quantum chemical calculation GUI software: "MoCalc2012".
[0103] Figure 2 is the FT-IR spectrum of glutaric acid (calculated and measured). Figure 2 The results shown in , confirmed that glutaric acid exists mainly in the form of a monomer or a chain dimer. Figure 3 is the FT-IR spectrum of adipic acid (calculated and measured). Figure 3 The results shown in , confirmed that adipic acid exists mainly in the form of a cyclic dimer. In addition, FT-IR measurements were also performed on pimelic acid (number of atoms in the main chain: 5), suberic acid (number of atoms in the main chain: 6), azelaic acid (number of atoms in the main chain: 7), and sebacic acid (number of atoms in the main chain: 8). The results confirmed that compounds with an odd number of atoms in the main chain exist mainly in the form of a monomer or a chain dimer, similar to glutaric acid, and compounds with an even number of atoms in the main chain exist mainly in the form of a cyclic dimer, similar to adipic acid.
[0104] As compounds having 4, 6 or 8 or more constituent atoms in the main chain, for example, adipic acid, suberic acid, sebacic acid, hexadecanedioic acid, dithiodiglycolic acid, 3,3'-dithiodipropionic acid, 4,4'-dithiodipropionic acid, etc. can be cited. These can be used alone or in combination of two or more. Among them, from the viewpoint that the wettability of the solder to the metal of the connecting portion can be more fully suppressed even if the laminated film is placed for a long time under room temperature, adipic acid, suberic acid, sebacic acid, and hexadecanedioic acid are preferred. In addition, compounds having 4, 6 or 8 or more constituent atoms in the main chain are compounds that do not contain any of an aromatic ring and an aliphatic ring. Compounds containing at least one of an aromatic ring and an aliphatic ring are classified as compounds having an aromatic ring or compounds having an aliphatic ring.
[0105] From the viewpoint of being able to more fully suppress the reduction in wettability of the solder to the metal of the connecting part even when the laminated film is left for a long time in a room temperature environment and then used, the number of constituent atoms of the main chain in the compound having 4, 6 or 8 or more can be 4, 6 or 8 to 14, or can also be 4, 6 or 8.
[0106] Examples of the main chain constituent atoms in the compound having 4, 6 or 8 or more main chain constituent atoms include carbon atoms, sulfur atoms and oxygen atoms. The main chain constituent atoms may be carbon atoms, sulfur atoms or carbon atoms.
[0107] From the viewpoint of being able to more fully suppress the reduction in wettability of the solder to the metal of the connecting part even when the laminate film is left for a long time in a room temperature environment and then used, the compound having 4, 6 or 8 or more constituent atoms in the main chain may include a compound represented by the following general formula (1) or a compound represented by the following general formula (2).
[0108]
[0109] In formula (1), R 1 represents a hydrogen atom or a monovalent organic group, and n represents an integer of 4, 6, or 8 to 14. 1 They may be the same as or different from each other.
[0110]
[0111] In formula (2), n represents 4, 6 or an integer of 8 to 14.
[0112] As the compound having an aromatic ring, phthalic acid, isophthalic acid, and terephthalic acid can be cited. These can be used alone or in combination of two or more. Among them, phthalic acid and isophthalic acid are preferred from the viewpoint of being able to more fully suppress the reduction in wettability of the solder to the metal of the connecting portion even when the laminated film is left for a long time at room temperature.
[0113] As the compound having an aliphatic ring, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, etc. can be cited. These can be used alone or in combination of two or more. Among them, 1,3-cyclohexanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid are preferred from the viewpoint of being able to more fully suppress the reduction in the wettability of the solder to the metal of the connection portion even when the laminated film is left for a long time at room temperature.
[0114] The melting point of the component (d) is preferably 50°C or more, more preferably 60°C or more, further preferably 70°C or more, particularly preferably 100°C or more, and preferably 200°C or less, more preferably 180°C or less, and further preferably 160°C or less. When the melting point of the component (d) is 200°C or less, it is easy to fully manifest the flux activity before the curing reaction of the thermosetting resin and the curing agent occurs. Therefore, according to the adhesive layer containing such a component (d), when the chip is mounted, the component (d) melts and the oxide film on the solder surface is removed, so that a semiconductor device with better connection reliability can be realized. In addition, when the melting point of the component (d) is 50°C or more, the reaction at room temperature or on a high temperature workbench is difficult to start, so that the storage stability is better. From these viewpoints, the melting point of the component (d) is preferably 50 to 200°C, more preferably 60 to 200°C, further preferably 70 to 180°C, and particularly preferably 100 to 160°C. In particular, when the melting point of the component (d) is 100 to 160° C., even when the laminated film is used after being left at room temperature for a long time, the decrease in wettability of the solder to the metal of the connection portion can be more fully suppressed.
[0115] The melting point of the component (d) can be measured using a conventional melting point measuring device. The sample used to measure the melting point is required to be crushed into a fine powder and used in a small amount to reduce the temperature deviation in the sample. As a container for the sample, a capillary with one end closed is usually used, but depending on the measuring device, there is also a device that is clamped between two microscope cover glasses as a container. In addition, when the temperature is raised sharply, a temperature gradient is generated between the sample and the thermometer, resulting in a measurement error. Therefore, it is desired that the heating when measuring the melting point be measured at a rate of increase of less than 1°C per minute.
[0116] As described above, since the sample is prepared into a fine powder, the sample before melting is opaque due to diffuse reflection of the surface. The temperature at which the appearance of the sample begins to become transparent is usually set as the lower limit of the melting point, and the temperature of complete melting is set as the upper limit. There are various forms of measuring devices. As the most classic device, a device is used in which a capillary containing a sample is installed on a double-tube thermometer and heated with a hot water bath. In order to attach the capillary to the double-tube thermometer, a liquid with high viscosity is used as the liquid of the hot water bath, usually concentrated sulfuric acid or silicone oil, and the sample is installed in a manner close to the liquid reservoir at the front end of the thermometer. In addition, as a melting point measuring device, a device that automatically determines the melting point while heating with a metal heating block, measuring the transmittance of light, and adjusting the heating can also be used.
[0117] In this specification, a melting point of 200°C or lower means that the upper limit of the melting point is 200°C or lower, and a melting point of 50°C or higher means that the lower limit of the melting point is 50°C or higher.
[0118] The acid dissociation constant pKa of the component (d) may be 5.0 or less or 4.6 or less. Furthermore, the acid dissociation constant pKa of the component (d) may be 2.0 or more, 2.5 or more, or 3.5 or more. When the acid dissociation constant pKa of the component (d) is 5.0 or less, sufficient flux activity can be obtained, and when it is 2.0 or more, the post-heat history reaction rate based on the heat history during temporary fixing can be reduced.
[0119] The content of component (d) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 1% by mass or more, based on the total solid content of the adhesive layer, and is preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 3% by mass or less. From the viewpoint of connection reliability and reflow resistance when manufacturing a semiconductor device and the viewpoint that the wettability of the solder to the metal of the connection portion can be more fully suppressed even if the laminated film is placed for a long time in a room temperature environment and then used, the content of component (d) is preferably 0.1 to 10% by mass, more preferably 0.5 to 5% by mass, and further preferably 1 to 3% by mass based on the total solid content of the adhesive layer. In addition, when the flux compound belongs to components (a) to (e), the content of component (d) is calculated as a compound that also belongs to component (d).
[0120] In the present embodiment, the equivalent ratio (carboxyl group / basic functional group, molar ratio) of the carboxyl group (acidic functional group) in the total amount of component (d) to the basic functional group in the total amount of component (c) is preferably 1.0 or more, and preferably 3.0 or less. The above-mentioned equivalent ratio is more preferably 1.3 or more, further preferably 1.5 or more, and more preferably 2.5 or less, and further preferably 2.0 or less.
[0121] (e) Filling
[0122] The adhesive layer may contain fillers (component (e)) as needed. Component (e) can be used to control the viscosity of the adhesive layer, the physical properties of the cured product of the adhesive layer, etc. Specifically, component (e) can, for example, suppress the generation of voids during connection, reduce the moisture absorption rate of the cured product of the adhesive layer, etc.
[0123] As the component (e), an insulating inorganic filler, whisker, resin filler, etc. can be used. Furthermore, as the component (e), one type may be used alone, or two or more types may be used in combination.
[0124] Examples of the insulating inorganic filler include glass, silica, alumina, titanium oxide, carbon black, mica, and boron nitride. Among them, silica, alumina, titanium oxide, and boron nitride are preferred, and silica, alumina, and boron nitride are more preferred.
[0125] Examples of the whiskers include aluminum borate, aluminum titanate, zinc oxide, calcium silicate, magnesium sulfate, and boron nitride.
[0126] Examples of the resin filler include fillers made of resins such as polyurethane and polyimide.
[0127] Compared with organic components (epoxy resin and curing agent, etc.), resin fillers have a smaller thermal expansion coefficient, so they are excellent in improving connection reliability. In addition, the viscosity of the adhesive layer can be easily adjusted by resin fillers. In addition, compared with inorganic fillers, resin fillers have excellent stress relief functions.
[0128] Inorganic fillers have a lower thermal expansion coefficient than resin fillers, so they can reduce the thermal expansion coefficient of the adhesive layer. In addition, most inorganic fillers have a controlled particle size, so viscosity adjustment is also easy.
[0129] Since the resin filler and the inorganic filler each have advantageous effects, either one may be used according to the application, or the two may be mixed and used in order to exert the functions of both.
[0130] The shape, particle size and content of the component (e) are not particularly limited. Furthermore, the component (e) may be a component whose physical properties are appropriately adjusted by surface treatment.
[0131] The content of component (e) is preferably 10% by mass or more, more preferably 15% by mass or more, based on the total solid content of the adhesive layer, and is preferably 80% by mass or less, more preferably 60% by mass or less. The content of component (e) is preferably 10 to 80% by mass, more preferably 15 to 60% by mass, based on the total solid content of the adhesive layer.
[0132] The component (e) is preferably composed of an insulator. When the component (e) is composed of a conductive material (for example, solder, gold, silver, copper, etc.), insulation reliability (especially HAST resistance) may be reduced.
[0133] (Other ingredients)
[0134] The adhesive layer may contain additives such as antioxidants, silane coupling agents, titanium coupling agents, leveling agents, and ion trapping agents. These can be used alone or in combination of two or more. The amounts thereof may be appropriately adjusted to achieve the effects of the additives.
[0135] An example of a method for preparing an adhesive layer (film-like adhesive) is shown below. First, components (a), (b), (c), and (d), and component (e) added as needed, etc. are added to an organic solvent, and dissolved or dispersed by stirring, mixing, etc. to prepare a resin varnish. Thereafter, the resin varnish is applied to a substrate film subjected to a demolding treatment using a knife coater, a roll coater, an applicator, etc., and then the organic solvent is removed by heating, thereby forming an adhesive layer (film-like adhesive) on the substrate film.
[0136] The thickness of the adhesive layer is not particularly limited, and is, for example, preferably 0.5 to 1.5 times, more preferably 0.6 to 1.3 times, and even more preferably 0.7 to 1.2 times the height of the bump before connection.
[0137] When the thickness of the adhesive layer is more than 0.5 times the height of the bump, the voids caused by the lack of adhesive filling can be fully suppressed, and the connection reliability can be further improved. In addition, when the thickness is less than 1.5 times, the amount of adhesive squeezed out of the chip connection area during connection can be fully suppressed, thereby fully preventing the adhesive from adhering to unnecessary parts. When the thickness of the adhesive layer is greater than 1.5 times, the bump must exclude a large amount of adhesive, which is prone to poor conduction. In addition, for the weakening of the bump caused by narrow pitch and multi-terminal (miniaturization of the bump diameter), excluding a large amount of resin will increase the damage to the bump, so it is not preferred.
[0138] Considering that the height of the bump is generally 5 to 100 μm, the thickness of the adhesive layer is preferably 2.5 to 150 μm, and more preferably 3.5 to 120 μm.
[0139] As the organic solvent used in the preparation of the resin varnish, it is preferred to have an organic solvent that can uniformly dissolve or disperse the various components, for example, dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide, diethylene glycol dimethyl ether, toluene, benzene, xylene, methyl ethyl ketone, tetrahydrofuran, ethyl cellosolve, ethyl cellosolve acetate, butyl cellosolve, dioxane, cyclohexanone and ethyl acetate. These organic solvents can be used alone or in combination of two or more. Stirring, mixing and kneading when preparing the resin varnish can be carried out using, for example, a stirrer, a crushing machine, a three-roll mill, a ball mill, a bead mill or a homogenizing disperser.
[0140] The substrate film is not particularly limited as long as it is a film having heat resistance that can withstand the heating conditions for volatilizing the organic solvent, and examples thereof include polyolefin films such as polypropylene films and polymethylpentene films, polyester films such as polyethylene terephthalate films and polyethylene naphthalate films, polyimide films, and polyetherimide films. The substrate film is not limited to a single-layer film composed of these films, and may also be a multilayer film composed of two or more materials.
[0141] The drying conditions for volatilizing the organic solvent from the resin varnish applied to the substrate film are preferably set to the conditions for sufficient volatilization of the organic solvent, specifically, preferably heating at 50 to 200° C. for 0.1 to 90 minutes. The organic solvent is preferably removed to 1.5% by mass or less relative to the total amount of the adhesive layer.
[0142] From the perspective of being able to further remove voids during curing under a pressurized atmosphere and obtaining better reflow resistance, the minimum melt viscosity of the adhesive layer is preferably 200 to 10,000 Pa·s, and more preferably 200 to 5,000 Pa·s. The minimum melt viscosity can be measured using a melt viscosity measuring device under the conditions of a measurement temperature of 0 to 200°C, a heating rate of 10°C / min, a frequency of 10 Hz, and a strain of 1%. The temperature (melting temperature) at which the adhesive layer shows the minimum melt viscosity is preferably 100 to 250°C, more preferably 120 to 230°C, and further preferably 140 to 200°C.
[0143] From the viewpoint of facilitating temporary fixing of semiconductor chips in a temperature range of 60 to 170° C., the melt viscosity of the adhesive layer at 80° C. is preferably 2000 to 30000 Pa·s, and the melt viscosity at 130° C. is preferably 400 to 20000 Pa·s, more preferably 4000 to 20000 Pa·s at 80° C. and 400 to 5000 Pa·s at 130° C. The melt viscosity can be measured by the above method using a melt viscosity measuring device.
[0144] (Back grinding tape 4)
[0145] The back grinding tape may include one or more pressure-sensitive adhesive layers and one or more base layers, or may be composed of one pressure-sensitive adhesive layer and one base layer. The laminated film of this embodiment can have both back grinding and circuit component connection. In this case, the adhesive layer is attached to the main surface of the semiconductor wafer on which the electrode side is provided.
[0146] The pressure-sensitive adhesive layer has adhesive strength at room temperature, preferably has the necessary adhesion to the adherend. In addition, it is preferred to have the property of curing (reducing adhesive strength) by high-energy rays such as radiation or heat, and more preferably can be easily peeled from the adhesive layer even without applying high-energy rays such as radiation or heat. In addition, the pressure-sensitive adhesive layer can be a pressure-sensitive type pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer can be formed using, for example, acrylic resins, various synthetic rubbers, natural rubbers, and polyimide resins.
[0147] The thickness of the pressure-sensitive adhesive layer may be 5 to 100 μm, or 10 to 80 μm.
[0148] As the substrate layer, for example, plastic films such as polyester film, polytetrafluoroethylene film, polyethylene film, polypropylene film, polymethylpentene film, etc. can be cited. Among them, polyester film is preferred, and polyethylene terephthalate film is more preferred. In addition, the substrate layer can be a layer in which two or more selected from the above materials are mixed or a layer in which the above films are multilayered.
[0149] The thickness of the substrate layer may be 10 to 100 μm, or 20 to 80 μm.
[0150] The thickness of the back grinding tape may be 10 to 200 μm, or 20 to 150 μm.
[0151] <Semiconductor devices>
[0152] A semiconductor device manufactured using the laminated film according to the present embodiment is described. The semiconductor device according to the present embodiment is a semiconductor device in which the connection parts of a semiconductor chip and a wiring circuit board are electrically connected to each other, or a semiconductor device in which the connection parts of a plurality of semiconductor chips are electrically connected to each other. In the semiconductor device according to the present embodiment, for example, a flip chip connection that can be electrically connected via an adhesive layer can be used.
[0153] Figure 4 Schematic cross-sectional view showing an embodiment of a semiconductor device (COB type connection method of a semiconductor chip and a substrate). Figure 4 As shown, the semiconductor device 100 includes: a semiconductor chip 12 and a substrate (wiring circuit substrate) 14 facing each other; wirings 15 respectively arranged on the facing surfaces of the semiconductor chip 12 and the substrate 14; connection bumps 30 connecting the wirings 15 of the semiconductor chip 12 and the substrate 14 to each other; and an adhesive layer 40 seamlessly filling the gap between the semiconductor chip 12 and the substrate 14. The semiconductor chip 12 and the substrate 14 are flip-chip connected through the wirings 15 and the connection bumps 30. The wirings 15 and the connection bumps 30 are sealed by the adhesive layer 40 and isolated from the external environment.
[0154] Figure 5 FIG. 1 is a schematic cross-sectional view showing another embodiment of a semiconductor device (a COC type connection method between semiconductor chips). Figure 5 As shown, in the semiconductor device 300 , two semiconductor chips 12 are flip-chip connected via wiring 15 and connection bumps 30 , and other points are the same as the semiconductor device 100 .
[0155] The semiconductor chip 12 is not particularly limited, and various semiconductors can be used, such as element semiconductors made of the same element such as silicon and germanium, and compound semiconductors such as gallium arsenide and indium phosphide.
[0156] The substrate 14 is not particularly limited as long as it is a wiring circuit substrate. It can be a circuit substrate in which wiring (wiring pattern) is formed by etching away unnecessary parts of a metal layer formed on the surface of an insulating substrate mainly composed of glass epoxy resin, polyimide, polyester, ceramic, epoxy resin, bismaleimide triazine, polyimide, etc., a circuit substrate in which wiring (wiring pattern) is formed on the surface of the above-mentioned insulating substrate by metal plating, etc., a circuit substrate in which wiring (wiring pattern) is formed by printing a conductive material on the surface of the above-mentioned insulating substrate, etc.
[0157] The connection parts such as the wiring 15 contain gold, silver, copper, solder (main components such as tin-silver, tin-lead, tin-bismuth, tin-copper), nickel, tin, lead, etc. as main components, and may contain a plurality of metals.
[0158] A metal layer with gold, silver, copper, solder (main components such as tin-silver, tin-lead, tin-bismuth, tin-copper, etc.), tin, nickel, etc. as main components can be formed on the surface of the wiring (wiring pattern). The metal layer can be composed of only a single component or a plurality of components. In addition, a structure in which a plurality of metal layers are stacked can be provided. Copper and solder are widely used because they are cheap and therefore preferred, but flux activity is required because of the presence of oxides or impurities.
[0159] Furthermore, you can also Figure 4 or Figure 5 The semiconductor device (package) shown is stacked and electrically connected using gold, silver, copper, solder (main components such as tin-silver, tin-lead, tin-bismuth, tin-copper), tin, nickel, etc. Copper and solder are widely used because they are cheap, so they are preferred, but flux activity is required due to the presence of oxides or impurities. For example, as seen in TSV technology, an adhesive layer can be placed between semiconductor chips to perform flip-chip connection or stacking, forming a hole that penetrates the semiconductor chip and connects to the electrode on the pattern surface.
[0160] Figure 6 1 is a schematic cross-sectional view showing another embodiment of a semiconductor device (a stacked semiconductor chip method (TSV)). Figure 6In the semiconductor device 500 shown in FIG. 1 , the wiring 15 formed on the interposer 50 is connected to the wiring 15 of the semiconductor chip 12 via the connection bump 30, thereby the semiconductor chip 12 is flip-chip connected to the interposer 50. The gap between the semiconductor chip 12 and the interposer 50 is filled with an adhesive layer 40 without a gap. On the surface of the semiconductor chip 12 on the side opposite to the interposer 50, the semiconductor chip 12 is repeatedly stacked via the wiring 15, the connection bump 30 and the adhesive layer 40. The wiring 15 on the pattern surface of the front and back sides of the semiconductor chip 12 is connected to each other through the through electrode 34 filled in the hole penetrating the inside of the semiconductor chip 12. In addition, as the material of the through electrode 34, copper, aluminum, etc. can be used.
[0161] By using this TSV technology, signals can be obtained from the back side of a semiconductor chip that is not normally used. In addition, since the through electrode 34 is vertically penetrated into the semiconductor chip 12, the distance between the opposing semiconductor chips 12 or between the semiconductor chip 12 and the interposer 50 can be shortened, making the connection flexible. In this TSV technology, the adhesive layer of the laminated film involved in this embodiment can be used as a sealing material between the opposing semiconductor chips 12 or between the semiconductor chip 12 and the interposer 50.
[0162] Furthermore, in a bump forming method with a high degree of freedom, such as the area bump chip technology, the semiconductor chip can be directly mounted on the motherboard without passing through an interposer. In such a case where the semiconductor chip is directly mounted on the motherboard, the adhesive layer of the laminated film involved in this embodiment can also be applied. In addition, in the case of stacking two wiring circuit substrates, the adhesive layer of the laminated film involved in this embodiment can also be applied when sealing the gap between the substrates.
[0163] <Method for manufacturing semiconductor device>
[0164] The method for manufacturing a semiconductor device according to the present embodiment includes: a step of laminating the surface of the laminate film on the adhesive layer side to a semiconductor wafer (laminating step); a step of grinding the back of the semiconductor wafer (back grinding step); a step of singulating the semiconductor wafer to obtain a semiconductor chip with an adhesive layer (singularization step); a step of attaching the semiconductor chip to a wiring circuit substrate, a semiconductor wafer or another semiconductor chip via the adhesive layer (bonding step). The method for manufacturing a semiconductor device according to the present embodiment may include a step of curing the adhesive layer after the bonding step and sealing at least a portion of the connection portion by the cured adhesive layer (sealing step).
[0165] In the lamination process, the adhesive layer side surface of the laminate film is bonded to the semiconductor wafer, and the adhesive layer, pressure-sensitive adhesive layer and base layer are laminated on the conductor wafer in this order. When the laminate film has a base film on the adhesive layer, the base film is peeled off before lamination.
[0166] In the back grinding step, the surface of the semiconductor wafer opposite to the side on which the adhesive layer and the like are laminated is ground to thin the semiconductor wafer.
[0167] In the singulation process, the grinding side of the thinned semiconductor wafer is attached to the dicing tape, and the semiconductor wafer and the adhesive layer are cut using a dicing device to obtain semiconductor chips with adhesive layers formed by the singulated semiconductor chips and the cut adhesive layer. The back grinding tape composed of the base material layer and the pressure-sensitive adhesive layer is peeled off from the adhesive layer before dicing.
[0168] In the bonding step, a semiconductor chip and a printed circuit board, a semiconductor chip and a semiconductor wafer, or a semiconductor chip and another semiconductor chip are connected via an adhesive layer.
[0169] When the bonding process is a process of connecting a semiconductor chip (hereinafter referred to as the "first semiconductor chip") to another semiconductor chip (hereinafter referred to as the "second semiconductor chip") via an adhesive layer, the bonding process may include: a process of arranging a plurality of second semiconductor chips on a workbench; and a process of temporarily fixing the workbench to 60 to 155° C. and arranging the first semiconductor chip in sequence on each of the plurality of second semiconductor chips arranged on the workbench via an adhesive layer to obtain a plurality of stacked bodies in which the second semiconductor chips, adhesive layers and first semiconductor chips are stacked in sequence.
[0170] Furthermore, when the bonding process is a process of connecting a semiconductor chip to a wiring circuit substrate, or a semiconductor chip to a semiconductor wafer via an adhesive layer, the bonding process may include: a process of configuring the wiring circuit substrate or the semiconductor wafer on a workbench; and a temporary fixing process of heating the workbench to 60-155°C and sequentially configuring a plurality of semiconductor chips on the wiring circuit substrate or the semiconductor wafer configured on the workbench via an adhesive layer to obtain a stacked body formed by sequentially stacking a wiring circuit substrate, an adhesive layer and a plurality of semiconductor chips, or a stacked body formed by sequentially stacking semiconductor wafers, an adhesive layer and a plurality of semiconductor chips.
[0171] In the temporary fixing step, the semiconductor chip with the adhesive layer is picked up, adsorbed onto a crimping tool (crimping head) of a crimping machine, and temporarily fixed to a wiring circuit board, another semiconductor chip, or a semiconductor wafer.
[0172] In the temporary fixing process, the connection parts need to be aligned in order to electrically connect them to each other, and therefore, a pressure bonding machine such as a flip chip bonder is generally used.
[0173] When the crimping tool picks up the semiconductor chip for temporary fixing, the crimping tool is preferably at a low temperature so that heat is not transferred to the adhesive layer on the semiconductor chip. On the other hand, when crimping (temporary crimping), the semiconductor chip is preferably heated to a high temperature so that the fluidity of the adhesive layer can be increased to effectively eliminate the voids involved. However, it is preferably heated to a curing reaction start temperature lower than the adhesive layer. In order to shorten the cooling time, the difference between the temperature of the crimping tool when picking up the semiconductor chip and the temperature of the crimping tool during temporary fixing is preferably small. The temperature difference is preferably less than 100°C, more preferably less than 60°C, and more preferably substantially 0°C. When the temperature difference is more than 100°C, since the cooling of the crimping tool takes time, there is a tendency to reduce productivity. The curing reaction start temperature of the adhesive layer refers to the start temperature when measured using DSC (PerkinElmer Co., Ltd. manufactured, DSC-Pyirs1) under the conditions of a sample amount of 10mg, a heating rate of 10°C / minute, and air or nitrogen atmosphere.
[0174] The load applied for temporary fixation is appropriately set in consideration of the number of connection parts, the absorption of height deviations of the connection parts, the amount of deformation of the connection parts, and the like. In the temporary fixation process, it is preferred that the opposing connection parts are in contact with each other after crimping (temporary crimping). When the connection parts are in contact with each other after crimping, metal bonds of the connection parts are easily formed in the crimping (main crimping) in the sealing process, and there is a tendency for less clogging of the adhesive layer. In order to eliminate gaps and contact of the connection parts, it is preferred that the load is large, for example, preferably 0.0001 to 0.2N, preferably 0.009 to 0.2N, and more preferably 0.001 to 0.1N per connection part (for example, a bump).
[0175] From the viewpoint of improving productivity, the pressing time in the temporary fixing step is preferably as short as possible, and may be, for example, 5 seconds or less, 3 seconds or less, or 2 seconds or less.
[0176] The heating temperature of the workbench is a temperature lower than the melting point of the connecting part, and can be generally 60 to 155° C., 65 to 120° C., or 70 to 100° C. By heating at such a temperature, voids entangled in the adhesive layer can be effectively eliminated. In addition, the heating temperature of the workbench is not actually applied to the adhesive layer itself.
[0177] As described above, the temperature of the pressure bonding tool during temporary fixing is preferably set to be small in temperature difference from the temperature of the pressure bonding tool during pickup of the semiconductor chip, and may be, for example, 80 to 350°C or 100 to 170°C.
[0178] When the bonding process includes the above-mentioned temporary fixing process, in the sealing process after the temporary fixing process, the adhesive layers in the multiple laminates or the laminates with multiple semiconductor chips can be cured together or separately and the multiple connecting parts can be sealed together or separately. Through the sealing process, the opposing connecting parts are bonded by metal bonds, and the gaps between the connecting parts are usually filled by the adhesive layer. In the sealing process, the metal of the connecting part can be heated to above the melting point, and a device that can be pressurized can be used. As examples of devices, a pressurized reflow furnace and a pressurized oven can be cited.
[0179] Regarding the heating temperature (connection temperature) of the sealing process, it is preferred to heat at a temperature above the melting point of the metal of at least one of the opposing connecting parts (e.g., bump-bump, bump-pad, bump-wiring). When the metal of the connecting part is solder, the heating temperature is preferably above 200°C and below 450°C. When the heating temperature is low, the metal of the connecting part may not melt and no sufficient metal bond may be formed. When the heating temperature is too high, there is a tendency that the void suppression effect becomes relatively poor or the solder is easy to scatter.
[0180] When a crimping machine is used to pressurize the joint, since the heat of the crimping machine is difficult to transfer to the adhesive layer (rounded corners) protruding from the side of the connection part, it is usually necessary to perform a heating treatment for fully curing the adhesive layer after crimping (main crimping). Therefore, the pressurization in the sealing process is preferably performed by air pressure in a pressurized reflow furnace, a pressurized oven, etc. instead of using a crimping machine. When pressurization is performed by air pressure, heat can be applied to the whole, and the heating treatment after crimping (main crimping) can be shortened or exempted, thereby improving productivity. Moreover, when pressurization is performed by air pressure, it is easy to perform the main crimping of multiple stacks (temporary fixed bodies) or stacks (temporary fixed bodies) with multiple semiconductor chips temporarily fixed at the same time. In addition, from the viewpoint of suppressing rounded corners, it is still preferred to pressurize by air pressure rather than directly pressurize using a crimping machine. Suppressing rounded corners is important for the trend of miniaturization and high density of semiconductor devices.
[0181] The atmosphere for pressure bonding in the sealing step is not particularly limited, but an atmosphere including air, nitrogen, formic acid, or the like is preferred.
[0182] The crimping pressure in the sealing process can be appropriately set according to the size and number of the parts to be connected. The pressure can be, for example, greater than atmospheric pressure and less than 1 MPa. From the perspective of suppressing voids and improving connectivity, a high pressure is preferred, and from the perspective of suppressing fillets, a low pressure is preferred. Therefore, the pressure is more preferably 0.05 to 0.5 MPa.
[0183] The crimping time varies according to the constituent metal of the connection portion. From the viewpoint of improving productivity, the shorter the time, the better. When the connection portion is a solder bump, the connection time is preferably less than 20 seconds, more preferably less than 10 seconds, and further preferably less than 5 seconds. In the case of copper-copper or copper-gold metal connections, the connection time is preferably less than 60 seconds.
[0184] When a plurality of semiconductor chips are stacked three-dimensionally as in a semiconductor device with a TSV structure, the plurality of semiconductor chips may be stacked one by one and temporarily fixed, and then the stacked plurality of semiconductor chips may be heated and pressurized together to obtain a semiconductor device.
[0185] Example
[0186] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the Examples.
[0187] The compounds used in each of the Examples and Comparative Examples are as follows.
[0188] (a) Ingredients: Thermoplastic resin
[0189] Phenoxy resin (manufactured by NIPPON STEEL Chemical & Material Co., Ltd., product name "FX293", Tg: about 160°C, Mw: about 30,000, biphenylfluorene type phenoxy resin)
[0190] (b) Ingredients: Thermosetting resin
[0191] ·Bisphenol F type liquid epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "YL983U")
[0192] Liquid epoxy resin (Mitsubishi Chemical Corporation, product name "YX7110B80")
[0193] · A polyfunctional solid epoxy resin containing a trisphenol methane skeleton (manufactured by Mitsubishi Chemical Corporation, product name "EP1032H60")
[0194] (c) Component: Curing agent
[0195] Imidazole curing agent (manufactured by SHIKOKU CHEMICALS CORPORATION, product name "2PHZ-PW", 2-phenyl-4,5-dihydroxymethylimidazole)
[0196] (d) Ingredient: Flux compound
[0197] Glutaric acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 98°C, molecular weight: 132, compound having 3 constituent atoms (carbon atoms) in the main chain)
[0198] Adipic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 152°C, molecular weight: 146, compound having 4 constituent atoms (carbon atoms) in the main chain)
[0199] · Pimelic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 105°C, molecular weight: 160, compound having 5 constituent atoms (carbon atoms) in the main chain)
[0200] Suberic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 142°C, molecular weight: 174, compound having 6 constituent atoms (carbon atoms) in the main chain)
[0201] · Azelaic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 98°C, molecular weight: 188, compound having 7 constituent atoms (carbon atoms) in the main chain)
[0202] · Sebacic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 135°C, molecular weight: 202, compound having 8 constituent atoms (carbon atoms) in the main chain)
[0203] Undecanedioic acid (manufactured by Tokyo Chemical Industry Co., Ltd., melting point: 109°C, molecular weight: 216, compound having 9 constituent atoms (carbon atoms) in the main chain)
[0204] Hexadecanedioic acid (manufactured by Tokyo Chemical Industry Co., Ltd., melting point: 126°C, molecular weight: 286, compound having 14 constituent atoms (carbon atoms) in the main chain)
[0205] Phthalic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 210°C, molecular weight: 166, a compound having an aromatic ring)
[0206] ·Isophthalic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 350°C, molecular weight: 166, a compound having an aromatic ring)
[0207] 1,3-Cyclohexanedicarboxylic acid (cis-, trans-mixture) (manufactured by Tokyo Chemical Industry Co., Ltd., melting point: 136° C., molecular weight: 172, compound having an aliphatic ring)
[0208] (e) Ingredients: Filler
[0209] Acrylic rubber particles (organic filler, manufactured by DOW, product name "EXL2655")
[0210] ·Methacrylic acid surface treated silica filler (inorganic filler, manufactured by Admatechs Co. Ltd., product name "KE180G-HLA", average particle size: about 180 nm)
[0211] The weight average molecular weight (Mw) of the component (a) is determined by the GPC method. The details of the GPC method are as follows.
[0212] Apparatus name: HPLC-8020 (product name, manufactured by TOSOH CORPORATION)
[0213] Chromatographic columns: 2 GMHXL + 1 G-2000XL
[0214] Detector: RI detector
[0215] Column temperature: 35°C
[0216] Flow rate: 1mL / min
[0217] Standard material: polystyrene
[0218] [Examples 1 to 8 and Comparative Examples 1 to 3]
[0219] <Preparation of film adhesive (adhesive layer)>
[0220] Thermoplastic resin, thermosetting resin, curing agent, flux compound and filler in the amounts (unit: mass parts) shown in Table 1 were added to an organic solvent (cyclohexanone) so that the NV value ([mass of the coating after drying] / [mass of the coating before drying]×100) was 50%. Zirconia beads and Zirconia beads of 1000 g were added to the same container and stirred for 30 minutes using a ball mill (manufactured by Fritsch Japan Co., Ltd., product name "Planetary Mill P-7"). After stirring, the zirconia beads were removed by filtration to prepare a coating varnish.
[0221] The obtained coating varnish was applied onto a substrate film (manufactured by Teijin Film Solutions Limited, product name "Purex A55") using a small precision coating device (manufactured by Yasui Seiki Inc.) and dried (100°C / 10 min) in a clean oven (manufactured by ESPEC CORP.) to obtain a film-like adhesive (adhesive layer) having a film thickness of 10 μm.
[0222] <Manufacturing of back grinding tape (pressure-sensitive adhesive tape)>
[0223] An acrylic copolymer using 2-ethylhexyl acrylate and methyl methacrylate as main monomers and hydroxyethyl acrylate and acrylic acid as functional group monomers was obtained by solution polymerization. The synthesized acrylic copolymer had a weight average molecular weight of 400,000 and a glass transition point of -38°C. A polyfunctional isocyanate crosslinking agent (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HL") was added to 100 parts by mass of the acrylic copolymer to prepare a varnish for a pressure-sensitive adhesive.
[0224] The pressure-sensitive adhesive varnish was applied onto a 25 μm thick polyethylene terephthalate (PET) substrate (manufactured by UNITIKA LTD., product name "Embred S25") using an applicator so that the thickness of the pressure-sensitive adhesive layer after drying would be 60 μm while adjusting the gap, and dried at 80° C. for 5 minutes. Thus, a back grinding tape having a pressure-sensitive type pressure-sensitive adhesive layer formed on a substrate layer was obtained.
[0225] <Production of laminated films>
[0226] Next, the above-mentioned back grinding tape consisting of a pressure-sensitive adhesive layer and a substrate layer was attached to the above-mentioned adhesive layer at 60°C, a linear pressure of 3kgf, and a speed of 5m / min in a manner that the adhesive layer was in contact with the pressure-sensitive adhesive layer, thereby obtaining a laminated film having a laminated structure of substrate film / adhesive layer / pressure-sensitive adhesive layer / substrate layer.
[0227] [evaluate]
[0228] The evaluation methods of the laminated films obtained in Examples and Comparative Examples are shown below. The evaluation results are shown in Table 1 or Table 2.
[0229] <Measurement of the rate of change of flux over time>
[0230] The laminated films obtained in the examples and comparative examples were left standing for 4 weeks at room temperature (23°C, 50% RH) to obtain laminated films after 4 weeks. The time-dependent change rate of the flux content in the adhesive layer was determined for the laminated films before and after 4 weeks of standing by the following method.
[0231] The adhesive layer obtained by peeling off the back grinding tape and the base film from the laminated film was cut into a size of 1.0 cm × 1.0 cm as a sample, and the FT-IR spectrum of the sample surface was measured using an ALPHA compact infrared spectrometer (manufactured by Bruker Optics KK, ATR method). In the obtained FT-IR spectrum, the peak intensity of the flux in the adhesive layer before being placed for 4 weeks was set as a, and the peak intensity of the flux in the adhesive layer after being placed for 4 weeks was set as b, and the time-dependent change rate (%) was calculated by the following formula. In addition, the peak intensities a and b are values obtained by adjusting the reference peak that does not change with time, which is different from the peak of the flux, to have the same intensity before and after being placed for 4 weeks.
[0232] Time-dependent change rate (%) = ((ba) / a) × 100
[0233] <Measurement of wettability>
[0234] The laminated films obtained in Examples and Comparative Examples were left standing for 4 weeks at room temperature (23° C., 50% RH) to obtain laminated films after 4 weeks of standing. The wettability of the laminated films before and after standing for 4 weeks was measured by the following method.
[0235] Using a desktop laminator (product name "Hotdog GK-13DX", manufactured by LAMI CORPORATION INC.), 4 adhesive layers obtained by peeling off the back grinding tape and the base film from the laminated film were stacked to make the film thickness 40μm, and then cut into a size of 7.5mm square, and attached to a plurality of semiconductor chips with solder bumps (chip size: 7.3mm×7.3mm, thickness 0.1mm, bump (connection part) height: about 45μm (total of copper column and solder), number of bumps: 1048 terminals, pitch 80μm, product name "WALTS-TEG CC80", manufactured by WALTS CO., LTD.) at 80°C. On another semiconductor chip (chip size: 17 mm × 17 mm, thickness 0.356 mm, number of bumps: 1048 terminals, pitch 80 μm, product name: WALTS-KIT CC80, manufactured by WALTS CO., LTD.), a semiconductor chip with an adhesive layer attached was pressed sequentially by heating and pressurizing using a flip chip bonder (FCB3, manufactured by Panasonic Corporation) to obtain a pressed laminate (mounted sample for evaluation). Regarding the pressing conditions, temporary pressing was performed while heating at 80°C / 30N / 1 second (set heating time during heating: 0.1 second), and then, under a pressure of 30N, the temperature was raised from 80°C to 200°C in 2 seconds, and the temperature was raised from 200°C to 300°C in 15 seconds, and after being kept at 300°C for 1 second, the temperature was lowered from 300°C to 200°C in 2 seconds, thereby performing the main pressing.
[0236] The obtained evaluation mounted sample was polished using a table polisher (Refine Polisher, manufactured by Refine Tec Ltd.) until the bump connection portion existing inside the chip was exposed. As a water-resistant polishing paper for polishing, a size of The water-resistant abrasive paper with a particle size of 1000 was replaced with water-resistant abrasive paper with a particle size of 2000, and then polished until the connection part was exposed. The exposed bump connection part was observed with SEM (product name "TM3030Plus desktop microscope", manufactured by Hitachi High-Tech Corporation), and the wettability of the solder on the upper surface of the Cu wiring was measured (the ratio of the width of the solder in the SEM cross-sectional image in contact with the upper surface of the Cu wiring to the width of the upper surface of the Cu wiring). The wettability is set as the average value of the values obtained by measuring 20 places. In addition, the decrease rate of the wettability B when using the laminated film after being placed for 4 weeks relative to the wettability A when using the laminated film placed 4 weeks ago (initial) was calculated (((AB) / A)×100).
[0237] <Evaluation of Connectivity>
[0238] For the evaluation mounted samples of Examples 1 to 3 and 8 and Comparative Examples 1 to 3 prepared in the above-mentioned measurement of wettability, the resistance value of the inner periphery of the chip was measured using a circuit tester (product name "POCKET TESTER 4300 COUNT", manufactured by CUSTOM) to evaluate the connectivity. Figure 7 The circuit diagram of the lower chip for installation (chip size: 17mm×17mm, thickness 0.356mm, number of bumps: 1048 terminals, pitch 80μm, product name "WALTS-KIT CC80", manufactured by WALTS CO., LTD.) is shown in the figure. In this circuit, the resistance value between terminal a and terminal b in the figure becomes the resistance value of the inner circumference of the chip. If the value of the resistance value is less than 35Ω, it means that the connection is good. If it is above 35Ω or the resistance value cannot be measured, it means that the connection is poor. The measurement results of the resistance value are shown in Table 2, and the "-" in the table indicates that the resistance value cannot be measured.
[0239] < 1 H-NMR measurement>
[0240] The laminated films obtained in Example 1 and Comparative Example 1 were placed under room temperature (23°C, 50% RH) for 4 weeks to obtain laminated films after being placed for 4 weeks. The back grinding tape (BGT) was peeled off from the laminated films before and after being placed for 4 weeks, and the obtained BGT was immersed in dimethyl sulfoxide-d6 at 25°C for 2 hours to extract the components. Thereafter, the supernatant was collected to obtain a BGT extract. Nuclear magnetic resonance (NMR) was performed on the BGT extract obtained from the initial laminated film (hereinafter, also referred to as "initial BGT extract"), the BGT extract obtained from the laminated film after being placed for 4 weeks (hereinafter, also referred to as "BGT extract after being placed for 4 weeks"), and the flux compounds (glutaric acid and adipic acid) used in Example 1 and Comparative Example 1, respectively. 1 H-NMR) measurement. The measurement conditions are as follows. 1 The H-NMR spectrum is shown in Figure 8 (Comparative Example 1) and Fig. 9 (Example 1).
[0241] Measurement device: Bruker Biospin ADVANCE NEO 400MHz+CryoProbe (manufactured by Bruker)
[0242] Observation core: 1 H
[0243] Resonance frequency: 400MHz
[0244] Measurement temperature: 25℃
[0245] Solvent: Dimethyl sulfoxide-d6, 99.9% (containing 0.05 vol% TMS)
[0246] Standard substance: Tetramethylsilane
[0247] like Figure 8 As shown, the initial BGT extract of Comparative Example 1, the BGT extract of Comparative Example 1 after 4 weeks of storage, and the glutaric acid 1 In the comparison of H-NMR spectra, the peaks in the frames of a and b observed in the glutaric acid monomer were not observed in the initial BGT extract, but were observed in the BGT extract after 4 weeks of storage. This shows that the glutaric acid was transferred from the adhesive layer to the pressure-sensitive adhesive layer due to the long-term storage of the laminated film at room temperature. On the other hand, Fig. 9 As shown, the initial BGT extract of Example 1, the BGT extract of Example 1 after 4 weeks of storage, and the adipic acid 1 In the comparison of H-NMR spectra, the peaks in the frames of a and b observed in adipic acid monomer were not observed in the initial BGT extract, and were almost not observed in the BGT extract after standing for 4 weeks. This shows that adipic acid can suppress the transfer from the adhesive layer to the pressure-sensitive adhesive layer compared to glutaric acid even when the laminated film is left for a long time at room temperature.
[0248]
[0249] [Table 2]
[0250]
[0251] Explanation of symbols
[0252] 1-adhesive layer (film adhesive), 2-base material layer, 3-pressure-sensitive adhesive layer, 4-back grinding tape, 10-laminated film, 12-semiconductor chip, 14-substrate, 15-wiring, 30-connection bump, 34-through electrode, 40-adhesive layer, 50-intermediate layer, 100, 300, 500-semiconductor device.
Claims
1. A laminate film comprising an adhesive layer, a pressure-sensitive adhesive layer and a substrate layer in this order, wherein the adhesive layer comprises a thermoplastic resin, a thermosetting resin, a curing agent and a flux compound having two carboxyl groups, wherein: The flux compound includes at least one selected from the group consisting of a compound having an aromatic ring, a compound having an aliphatic ring, and a compound having 4, 6, or 8 or more constituent atoms in a main chain.
2. The laminated film according to claim 1, wherein In the compound having 4, 6 or 8 or more constituent atoms in the main chain, the number of constituent atoms in the main chain is 4, 6 or 8.
3. The laminated film according to claim 1, wherein The compound having 4, 6 or 8 or more constituent atoms in the main chain includes a compound represented by the following general formula (1): In formula (1), R 1 represents a hydrogen atom or a monovalent organic group, n represents an integer of 4, 6 or 8 to 14, and there are plural R 1 They may be the same as or different from each other.
4. The laminated film according to claim 1, wherein The compound having 4, 6 or 8 or more constituent atoms in the main chain includes a compound represented by the following general formula (2): In formula (2), n represents an integer of 4, 6 or 8-14.
5. The laminated film according to claim 1, wherein The melting point of the flux compound is 100-160°C.
6. The laminated film according to claim 1, wherein The thermosetting resin includes an epoxy resin.
7. The laminated film according to claim 1, wherein The curing agent includes an amine curing agent.
8. The laminated film according to claim 1, wherein The curing agent includes an imidazole-based curing agent.
9. A method for manufacturing a semiconductor device, wherein the semiconductor device is a semiconductor device in which the connection portions of a semiconductor chip and a wiring circuit board are electrically connected to each other, or a semiconductor device in which the connection portions of a plurality of semiconductor chips are electrically connected to each other, The method for manufacturing a semiconductor device comprises: A step of bonding the surface of the laminate film according to any one of claims 1 to 8 on the adhesive layer side to a semiconductor wafer; A step of back grinding the semiconductor wafer; The step of singulating the semiconductor wafer to obtain semiconductor chips with adhesive layers; and A step of attaching the semiconductor chip to a printed circuit board, a semiconductor wafer or another semiconductor chip via the adhesive layer.
10. The method for manufacturing a semiconductor device according to claim 9, wherein: The process of attaching the semiconductor chip to a wiring circuit substrate, a semiconductor wafer or another semiconductor chip via the adhesive layer includes: a step of arranging a plurality of the other semiconductor chips on a workbench; and The stage is heated to 60 to 155° C. and the semiconductor chips are sequentially arranged on the plurality of other semiconductor chips arranged on the stage via the adhesive layer to obtain a plurality of stacked bodies in which the other semiconductor chips, the adhesive layer and the semiconductor chips are sequentially stacked.
11. The method for manufacturing a semiconductor device according to claim 9, wherein: The process of attaching the semiconductor chip to a wiring circuit substrate, a semiconductor wafer or another semiconductor chip via the adhesive layer includes: a step of placing the printed circuit board or the semiconductor wafer on a workbench; and The workbench is heated to 60-155°C and a plurality of the semiconductor chips are sequentially arranged on the wiring circuit substrate or the semiconductor wafer arranged on the workbench via the adhesive layer to obtain a stacked body formed by sequentially stacking the wiring circuit substrate, the adhesive layer and the plurality of semiconductor chips, or a temporary fixing process for a stacked body formed by sequentially stacking the semiconductor wafer, the adhesive layer and the plurality of semiconductor chips.
Citation Information
Patent Citations
Semiconductor device manufacturing method
JP2012222038A